The Effect of Labor Force Participation Rate (TPAK), Human Development Index (HDI), and Unemployment on Poverty in Central Java in 2022 - Grecia Adis Vanessa; Xie Guilin; Deng Jiao (Journal of Noesantara Islamic Studies, 2024)
This research aims to find out what percentage of the poverty rate is mushrooming in Central Java Province. According to the Central Bureau of Statistics (BPS) it was recorded that Central Java Province was ranked 13th out of 34 provinces in Indonesia in 2022 with Kebumen Regency having the highest percentage of 16.41% and Semarang city having the lowest percentage of poverty at 4.25 but all are just numbers because BPS only measures the consumption of staple foods which do not include side dishes and other snacks, For example, a family can eat rice a day with rice costing 12 thousand rupiah per kilo and is said to be able to afford it, it is precisely the social gap that is more pronounced even though we live in an area with minimal poverty but if we cannot compensate for it then we will feel the poorest and vice versa if we live in an area with a high percentage of poverty and we are able to balance the social situation or can exceed it then we will feel rich because every region whether it is a city or a regency feels the same even though it is often said that the regency is more like a village than a city even though it has different leaders, namely the mayor and regent who have their own privileges. In this study, 25% poverty is influenced by the Labor Force Participation Rate (TPAK), Human Development Index (HDI) and Unemployment which are also independent variables and poverty as the dependent variable, but the remaining 75% that affects poverty is outside the explanation of this model, but if the government is able to increase the percentage level of TPAK, HDI, and Unemployment, it will at least reduce the percentage level of poverty.